1999
DOI: 10.1128/aem.65.7.2853-2856.1999
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Kernel Age on Fumonisin B 1 Production in Maize by Fusarium moniliforme

Abstract: Production of fumonisins by Fusarium moniliforme on naturally infected maize ears is an important food safety concern due to the toxic nature of this class of mycotoxins. Assessing the potential risk of fumonisin production in developing maize ears prior to harvest requires an understanding of the regulation of toxin biosynthesis during kernel maturation. We investigated the developmental-stage-dependent relationship between maize kernels and fumonisin B1 production by using kernels collected at the blister (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…Kernel age could influence mycotoxin production in corn. FBs were mainly produced at dent stage in kernels characterized by a moisture level of 40%, whereas lower contamination was observed in kernels collected at the blister and milk stages (Warfield and Gilchrist 1999). Conversely, the onset of fungal infection and DON contamination was observed already at the blister and milk stages (Atanasova‐Penichon et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Kernel age could influence mycotoxin production in corn. FBs were mainly produced at dent stage in kernels characterized by a moisture level of 40%, whereas lower contamination was observed in kernels collected at the blister and milk stages (Warfield and Gilchrist 1999). Conversely, the onset of fungal infection and DON contamination was observed already at the blister and milk stages (Atanasova‐Penichon et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Warfield and Gilchrist () reported that the levels of mycotoxin in corn in the field increase as the corn grows. Teller et al .…”
Section: Discussionmentioning
confidence: 99%
“…According to these results, it is thought that the possibility of mycotoxin being produced during ensiling is low. On the other hand, mycotoxins in corn are known to increase during growing in the field (Warfield & Gilchrist ; Uegaki et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One such component is starch, which changes dramatically in the kernel as it approaches maturity (Ingle et al ., 1965). Immature kernels lacking starch do not support FB 1 biosynthesis or expression of fumonisin biosynthetic ( FUM ) genes, but as kernels approach maturity and accumulate starch, they support high levels of FB 1 production (Bluhm and Woloshuk, 2005; Warfield and Gilchrist, 1999). Growth of F. verticillioides is comparable throughout each stage of kernel development (Bluhm and Woloshuk, 2005), indicating that immature kernels either repress FB 1 biosynthesis or lack the ability to induce FUM gene expression.…”
Section: Introductionmentioning
confidence: 99%